Probiotics in the management of radiation-induced oral mucositis - Li, Yixuan; Li, Zixia; Zheng, Shuhao; Xu, Xin (Frontiers in Cellular and Infection Microbiology, 2024)
Oral mucositis is a common and debilitating oral complication in head and neck cancer patients undergoing radiotherapy, resulting in diminished quality of life and potential treatment disruptions. Oral microbiota has long been recognized as a contributing factor in the initiation and progression of radiation-induced oral mucositis (RIOM). Numerous studies have indicated that the radiation-induced oral microbial dysbiosis promotes the occurrence and severity of oral mucositis. Therefore, approaches that modulate oral microbial ecology are promising for the management of RIOM. Probiotics as a relatively predicable and safe measure that modulates microecology have garnered significant interest. In this review, we discussed the correlation between RIOM and oral microbiota, with a particular focus on the efficacy of probiotics in the control of RIOM, in order to provide novel paradigm for the management of this disease.